2017
DOI: 10.1186/s13054-017-1620-6
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines as outcome markers in isolated traumatic brain injury: the COMA-TBI study

Abstract: BackgroundElevated catecholamine levels might be associated with unfavorable outcome after traumatic brain injury (TBI). We investigated the association between catecholamine levels in the first 24 h post-trauma and functional outcome in patients with isolated moderate-to-severe TBI.MethodsA cohort of 174 patients who sustained isolated blunt TBI was prospectively enrolled from three Level-1 Trauma Centers. Epinephrine (Epi) and norepinephrine (NE) concentrations were measured at admission (baseline), 6, 12 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 36 publications
2
67
0
2
Order By: Relevance
“…Our group verified these results and showed that the odds of mortality were reduced with beta-blockers in patients with TBI by 65% in the adjusted regression model 14. These findings are consistent across multiple retrospective studies,9 10 12 14 15 19 20 32 but all share a similar weakness. Patients in most of these studies received ‘2 or more doses’, ‘greater than one dose’, or scheduled doses instead of actually titrating the dose of beta-blockers to a target 10 14 16 24 33 34.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our group verified these results and showed that the odds of mortality were reduced with beta-blockers in patients with TBI by 65% in the adjusted regression model 14. These findings are consistent across multiple retrospective studies,9 10 12 14 15 19 20 32 but all share a similar weakness. Patients in most of these studies received ‘2 or more doses’, ‘greater than one dose’, or scheduled doses instead of actually titrating the dose of beta-blockers to a target 10 14 16 24 33 34.…”
Section: Discussionsupporting
confidence: 83%
“…The etiology for the syndrome of dysautonomia or paroxysmal sympathetic hyperactivity18 is a catecholamine surge leading to tachycardia, fever, hypertension, diaphoresis, tachypnea, and mydriasis from cerebral disconnection 15. Multiple authors have shown the both central and peripheral catecholamines are elevated after TBI 4 6 13 17 32 41–43. The elevation of catecholamines is directly proportional to the severity of brain injury 4 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia in the injured brain as well as neutrophils in extra-cerebral areas generate inducible nitricoxide synthase early after TBI, which contributes to hemodynamic instability through vasodilation 148 . In contrast, vasoconstriction is induced by catecholamines from the TBI-activated HPAA, which results in a stress reaction that modulates extra-cerebral immune responses (for example, activation of neutrophils and immunological-metabolic shifts) and is also associated with a poor outcome 149 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…Another study by Rizoli et al . [ 25 ] confirmed that higher admission levels of E were associated with a higher risk of unfavorable outcome which was assessed at 6 months by the extended Glasgow outcome scale score (odds ratio [OR], 2.04, 95% confidence interval [CI]: 1.31–3.18, P = 0.002) and that higher admission levels of NE were associated with higher risk of unfavorable outcome (OR, 1.59, 95% CI: 1.07–2.35, P = 0.022). Other investigators have not found such a correlation.…”
Section: Discussionmentioning
confidence: 99%